1992
DOI: 10.1017/s0007485300042553
|View full text |Cite
|
Sign up to set email alerts
|

The influence of Dolichoderus thoracicus (Hymenoptera: Formicidae) on losses due to Helopeltis theivora (Heteroptera: Miridae), black pod disease, and mammalian pests in cocoa in Malaysia

Abstract: The influence of the black cocoa ant Dolichoderus thoracicus (Smith) on losses due to the mirid Helopeltis theivora Waterhouse, black pod disease (caused by Phytophthora palmivora (Peronosporales)) and mammalian pests (rats, squirrels and civet cats) was studied over a two-year period in two separate fields of cocoa. Both fields initially had high D. thoracicus activity. In each field, antscarce plots were created by treating these plots with insecticides; antabundant plots existed where the plots were left un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 16 publications
0
14
0
3
Order By: Relevance
“…In inoculation tests, we showed that Philidris workers and their nest material are highly infested with spores of P. palmivora. Dolichoderus workers had a certain infection potential, but it was much lower (see electronic supplementary material, Invertebrate vectors of Phytophthora have been observed before [3] and Dolichoderus ants were even discussed as possible vector [44]. But here we show that the transmission efficiency is highly associated to specific behavioural traits and may differ widely even between related species.…”
Section: (D) Ant Community Effects On Fruit Losses Owing To Diseasesmentioning
confidence: 54%
“…In inoculation tests, we showed that Philidris workers and their nest material are highly infested with spores of P. palmivora. Dolichoderus workers had a certain infection potential, but it was much lower (see electronic supplementary material, Invertebrate vectors of Phytophthora have been observed before [3] and Dolichoderus ants were even discussed as possible vector [44]. But here we show that the transmission efficiency is highly associated to specific behavioural traits and may differ widely even between related species.…”
Section: (D) Ant Community Effects On Fruit Losses Owing To Diseasesmentioning
confidence: 54%
“…In fact, arboreal ants attracted to hemipteran honeydew have long been utilized to control nonhoneydew-producing herbivore pests in several tree crops (Way & Khoo 1992). For example, growers manipulate colonies of Dolichoderus ants in cocoa (Theobroma cacao) and sapodilla (Manilkara zapota) plantations in Southeast Asia, because the mealy bug-tending ants protect cocoa pods and sapodilla fruits from damage by mirids (Heteroptera; Khoo & Ho 1992) and pyralid larvae (Lepidoptera; Van Mele & Cuc 2001) without any direct yield loss caused by the mealy bugs. However, far less is known about the net effects of ant-hemipteran interactions on herbaceous crop plants in more ephemeral systems, such as row and vegetable crops.…”
Section: Effects Of Ant-hemipteran Interactions On Host Plant Damage mentioning
confidence: 99%
“…A meta-analysis of studies in natural and agricultural systems showed that the greater the diversity of predators, the lower the herbivore community, and consequently, the growth and reproduction of plants increase (Schmitz et al, 2000). Besides affecting the community of herbivores, ants may also reduce fungal pathogens, eliminating spores (de la Fuente & Marquis, 1999) or restricting the interactions between plants and disease vectors (Khoo & Ho, 1992).…”
Section: Ant Communities and Habitat Complexitymentioning
confidence: 99%